Evaluation of Moral Education Program: Study at MI Tamrinussibyan 01 Al-Hikmah - Atqia, Qy; Utanto, Yuli; Kustiono, Kustiono (Universitas Negeri Semarang, 2021)
Noble characters are the main foundation in the formation of human personality. To form noble characters in life, there are needs for continuous guidance, especially at the level of Elementary School/Madrasah Ibtidaiyah. MI Tamrinussibyan 01 Al-Hikmah is the best private madrasah in Brebes Regency which has implemented a moral education program in madrasah. This study aims to evaluate the moral education program of MI Tamrinussibyan 01 Al-Hikmah. Evaluation is carried out on the aspects of planning, implementation, and results. This research used qualitative methods with direct observations in the field, digging up information through interviews with teachers, students, and parents. The results of this study are: (1) the planning of the moral education program in the human resources and infrastructure components still needs to be improved, (2) the implementation of the moral education program has been well integrated into all learning activities in schools, (3) the results of the moral education program in religious attitudes, honesty, manners are appropriate for the purpose, while the attitude of responsibility and compassion for the environment still needs to be improved. Implication of this study can be used as a reference for other schools in developing a moral education curriculum so that the results obtained are in accordance with the objectives to be achieved.